The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1159/000187361
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Children with Acute Renal Failure: A Study of 138 Cases

Abstract: Acute renal failure (ARF) in children has a poor prognosis in spite of modern therapeutic techniques. For this reason, it would be useful to have prognostic indicators early in the course of the disease, in order to identify those patients that could benefit most from aggressive treatment. In an attempt to establish valid prognostic factors, we prospectively studied 138 cases of ARF in children. We examined age, sex, etiology of ARF, previous surgery, prerenal origin, clinical situation of the patient when fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
(28 reference statements)
2
30
0
Order By: Relevance
“…Univariate analysis showed that the incidence of oliguria in our patients increased the risk of mortality by a multiple of 2.24 and that the incidence of anuria increased the risk of mortality by a multiple of 1.9. This association was observed by others [3, 5, 6, 12-14, 24, 31, 32] and is in contrast to results reported by Gallego et al [33]. Chew et al [12] carried out a detailed study and reported that of all the parameters of renal injury, oliguria was the most important and carried the greatest weight in multivariate analyses [12,34].…”
Section: Discussionmentioning
confidence: 77%
“…Univariate analysis showed that the incidence of oliguria in our patients increased the risk of mortality by a multiple of 2.24 and that the incidence of anuria increased the risk of mortality by a multiple of 1.9. This association was observed by others [3, 5, 6, 12-14, 24, 31, 32] and is in contrast to results reported by Gallego et al [33]. Chew et al [12] carried out a detailed study and reported that of all the parameters of renal injury, oliguria was the most important and carried the greatest weight in multivariate analyses [12,34].…”
Section: Discussionmentioning
confidence: 77%
“…Most pediatric studies have been from single centers and are limited by small sample size and a propensity to focus only on critical care populations or children who require dialysis (2,(14)(15)(16)(17)(18)(19)(20)(21)(22). Studies have suggested that the epidemiology of pediatric AKI has changed dramatically over the past few decades, noting that sepsis, congenital heart disease, and oncologic illness have replaced hemolytic uremic syndrome, GN, and primary renal diseases as the most common causes of AKI in hospitalized children (14,23).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional diuretics are used to augment urine output in these patients, but relative oliguria often persists and withdrawal of diuretic therapy may lead to clinical deterioration in multiple organ systems. Fluid imbalance can impair the ability of clinicians to deliver adequate nutrition and significantly increases the risk of mortality and morbidity in diureticdependent patients [1,2]. Effective alternative diuretics utilizing novel mechanisms of action may allow clinicians to minimize the toxicities of conventional diuretics in oliguric critically ill patients.…”
Section: Introductionmentioning
confidence: 99%